Fresno County Young Lawyers Association 7th Annual Justice George Hopper Memorial Luncheon - Watkins, Howard::::::::: (1988)
Rene Lastreto II, Justice David Eagleson, Deborah Byron, and Traci Scratch marks in middle of photograph